An R2R3-MYB transcription factor VyMYB24, isolated from wild grape Vitis yanshanesis J. X. Chen., regulates the plant development and confers the tolerance to drought - Zhu, Ziguo; Quan, Ran; Chen, Guangxia; Yu, Guanghui; Li, Xiujie; Han, Zhen; Xu, Wenwen; Li, Guirong; Shi, Jiangli; Li, Bo (Frontiers in Plant Science, 2022)
In grapevine, the MYB transcription factors play an important regulatory role in phenylpropanoid pathway including proanthocyanidin, anthocyanin and flavonol biosynthesis. But the role of MYB in abiotic stresses is not clear. Here, an R2R3-MYB transcription factor, VyMYB24, was isolated from a high drought-tolerant Chinese wild Vitis species V. yanshanesis. Our founding demonstrated that it was involved in plant development and drought tolerance. VyMYB24 is a nuclear protein and significantly induced by drought stress. When over-expressed in tobacco, VyMYB24 caused plant dwarfing including plant height, leaf area, flower size and seed weight. GA1+3 content in transgenic plants were reduced significantly, and spraying exogenous Gibberellin could recover the dwarf phenotype of VyMYB24 transgenic plants, suggesting that VyMYB24 might inhibit plant development by the regulation of GA metabolism. Under drought stress, the VyMYB24 transgenic plants improved the tolerance to drought with lower wilting rate, lower relative electrical conductivity and stronger roots. Compared with wild type, VyMYB24 transgenic plants accumulated less reactive oxygen, accompanied by increased antioxidant enzyme activity and up-regulation of superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT) genes. In addition, transgenic plants produced lower MDA concentration levels and accumulated more proline, and NtP5CR and NtP5CS genes were up-regulated significantly when exposed to drought. Besides, abiotic stress-responsive genes NtDREB, NtERD10C, NtERD10D and NtLEA5 genes were up-regulated significantly in VyMYB24 transgenic plants. These results indicate that VyMYB24 plays a positive regulatory role in response to drought stress and also regulates plant development, which provide new evidence to further explore the molecular mechanism on drought stress of MYB gene family.